2022
DOI: 10.1016/j.jcmgh.2021.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Regulation of Macrophages by SIRT1 Determines Activation During Cholestatic Liver Disease in Mice

Abstract: Here, we describe that the SIRT1/mTOR axis regulates metabolic rewiring, inflammasome activation, and autophagy in macrophages, in which SIRT1 overexpression actively contributes to aggravate cholestatic liver disease progression in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 73 publications
(208 reference statements)
0
11
0
Order By: Relevance
“…SIRT1 contributes to the function and biogenesis of mitochondria [ 33 ]. Of note, Samadi et al [ 34 ] described that SIRT1 expression is suppressed in a diabetic dry eye model.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 contributes to the function and biogenesis of mitochondria [ 33 ]. Of note, Samadi et al [ 34 ] described that SIRT1 expression is suppressed in a diabetic dry eye model.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that hepatic stellate cells (HSC)specific SIRT1 knockout mice were more susceptible to long-term chronic-plus-multiple binges of ethanol-induced liver fibrosis (160). In contrast, Isaacs-Ten et al found that SIRT1 promotes increased liver inflammation and injuries post-LPS/GalN and bile duct ligation, associated with elevated activation of inflammasomes in macrophages (163). These contradictory findings suggest that SIRT1 might be a promising target for therapeutic intervention in hepatic inflammatory diseases, but further investigation is required.…”
Section: Livermentioning
confidence: 99%
“…In contrast, Isaacs-Ten et al. found that SIRT1 promotes increased liver inflammation and injuries post-LPS/GalN and bile duct ligation, associated with elevated activation of inflammasomes in macrophages ( 163 ). These contradictory findings suggest that SIRT1 might be a promising target for therapeutic intervention in hepatic inflammatory diseases, but further investigation is required.…”
Section: Sirt1 In the Regulation Of Inflammationmentioning
confidence: 99%
“…In addition, SIRT1 regulates the expression of hypoxia-inducible factor 1α (HIF-1α) and vascular endothelial growth factor to modulate airway inflammation [ 48 ]. In contrast, SIRT1, through activating mTOR, contributes to hepatic inflammation, inflammasome activation, and liver injury [ 49 ]. Future studies will provide insights into the SIRT1 crosstalks to mTOR pathway to alleviate discrepancies in different experimental settings.…”
Section: Overview Of Sirtsmentioning
confidence: 99%
“…A growing body of literature suggests an essential role for SIRT1 in regulating immunometabolic pathways to impact the immune and inflammatory responses [ 49 , 50 ]. Upon TLR4 stimulation, SIRT1, coupling to a cofactor NAD + , regulates epigenetic reprogramming for the coordinated bioenergetic and inflammatory responses [ 51 , 52 ].…”
Section: Overview Of Sirtsmentioning
confidence: 99%